ASPEK STRUKTUR KEPEMILIKAN PADA NILAI PERUSAHAAN : PERAN MEDIASI KUALITAS LABA - Afrizon Afrizon; Renato Sitompul (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
The goal of this research is to find evidence that managerial and institutional ownership affect earnings quality, and that earnings quality mediates the effect of managerial and institutional ownership on firm value. Firm value is measured using Tobin's Q, earnings quality uses earnings persistence, managerial ownership uses INSDR and institutional ownership uses the percentage of share ownership divided by the company's total shares. This research was conducted on manufacturing companies from 2013 to 2017 and the sample used was 48 companies with a total of 240 observations. Path analysis was the analytical method used in this study. From these tests it is known that managerial ownership has a negative effect on earnings quality; institutional ownership has a positive effect on earnings quality; managerial ownership has no effect on firm value, institutional ownership has no effect on firm value. Earnings quality is not able to mediate the effect of managerial ownership on firm value, and conversely earnings quality is able to mediate the effect of institutional ownership on firm value